Influence of Pre‐organised Architecture on Cell Adhesion by Using Multivalent RGD Compounds. (10th February 2016) - Grassin, Adrien; Jourdan, Muriel; Dumy, Pascal; Boturyn, Didier
Abstract: Multimeric RGD‐containing compounds were designed to study the influence of ligand architecture on binding avidity. We report the synthesis of a series of tetrameric RGD compounds and their in vitro biological evaluation. The further application of molecular dynamic simulations for structural studies of RGD derivatives reveals that the observed affinities correlate with the accessibility of segregated RGD motif. Abstract : Grabbing with all four hands : Tetrameric RGD‐containing macromolecules were designed by varying the interligand distances. We show, by both biochemical investigation and molecular modelling, the importance of well pre‐organised architecture of multivalent RGD compounds for the binding avidity of αV β3 receptor.